Enhanced Lung Cancer Therapy via Co-Encapsulation of Docetaxel and Betulinic Acid - Trideep Saikia; Prakash Rajak; Bhanu P. Sahu; Lima Patowary (MDPI AG, 2024)
Docetaxel (DTX) and betulinic acid (BA) co-encapsulated poly-lactic co-glycolic acid (PLGA) nanoparticles (NPs) were developed for enhanced lung cancer activity in vitro. Poly (lactic-co-glycolic acid) (PLGA) was used as an encapsulating polymer along with polyvinyl alcohol (PVA) as a stabilizing base to formulate NPs with the double-emulsion solvent evaporation method to study the size and potential, along with the surface morphology and in vitro release, of NPs. Cell culture studies like in vitro cellular uptake, apoptosis, and cell cycle arrest were performed in an in vitro cytotoxicity study to access the NP's effect in the A549 human lung cancer cell line. The emulsification solvent evaporation technique produced smooth spherical nanoparticles of small sizes with a relatively narrow size distribution (147.2 ± 12.29 nm). On the A549 cell line, the formulation showed higher cytotoxicity (6.43 ± 0.11, 4.21 ± 0.32, and 1.17 ± 0.23 µmol for 24, 48, and 72 h, respectively) compared to the free drug due to an increase in vitro cellular uptake. Apoptosis and cell cycle analysis also confirmed the effectiveness of the prepared NPs. In vitro studies have proven the tumor-targeting potential of DTX-BA-NPs in A549 cell lines and could be future medication for lung cancer treatment.